COVID-19 among healthcare workers in a specialist infectious diseases setting in Naples, Southern Italy: results of a cross-sectional surveillance study. Issue 4 (August 2020) - Fusco, F.M.; Pisaturo, M.; Iodice, V.; Bellopede, R.; Tambaro, O.; Parrella, G.; Di Flumeri, G.; Viglietti, R.; Pisapia, R.; Carleo, M.A.; Boccardi, M.; Atripaldi, L.; et al.
Summary: A coronavirus disease 2019 (COVID-19) surveillance study was performed in March–April 2020 among asymptomatic healthcare workers (HCWs) at a specialist infectious diseases hospital in Naples, Italy. All HCWs underwent two rounds of molecular and serological testing for severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). One hundred and fifteen HCWs were tested; of these, two cases of infection were identified by reverse transcriptase polymerase chain reaction and two HCWs were SARS-CoV-2 immunoglobulin G seropositive. The overall prevalence of current or probable previous infection was 3.4%. The infection rate among HCWs was reasonably low. Most of the infected HCWs had been asymptomatic for the preceding 30 days, which supports the need for periodic screening of HCWs for COVID-19.